Focus realization in Romance and beyond - García, Marco García; Uth, Melanie (Studies in language companion series ;, 2018)
What are the linguistic means for expressing different types of foci such as (narrow) information focus and contrastive focus in Romance languages, and why are there such differing views on such a presumably clear-cut research subject? Bringing together original expert work from a variety of linguistic disciplines and perspectives such as language acquisition and language contact, this volume provides a state-of-the-art discussion on central issues of focus realization. These include the interaction between prosody, syntax, and pragmatics, the typology of word order and intonation languages, the differentiation between focus and related notions such as contrast and presupposed modality, and the role of synchronic variation and change. The studies presented in this volume cover a broad range of Romance languages, including French, Italian, Portuguese, and different varieties of Spanish. Moreover, the book also offers new insights into non-Romance languages such as English, German, and Quechua.